Strategi Menanamkan Karakter Religius Dan Kejujuran Dalam Pembelajaran Daring Di Sekolah Dasar - Fahriza Hilmi; Wahdan Najib Habiby (Jurnal Elementaria Edukasia, 2023)
This study aims to determine the online learning of Islamic character informing religious character and honesty in elementary schools. This research uses a qualitative approach with a case study type. Primary data was obtained through interviews with grade 4 and 5 teachers. Secondary data was obtained from books and journals related to the research theme as well as interviews with school principals. Data analysis was carried out through three stages, namely: data reduction, data presentation, and then drawing conclusions. Data triangulation was carried out through interviews with principals, and students to maintain validity.The research results obtained include: 1) The implementation of Islamic Religious Education learning during online learning at SD Negeri 2 Tigajuru runs using WA group as the main media, while implementation outside Islamic Education learning occasionally uses Google Classroom or Zoom Meeting. 2) The strategy of cultivating religious character towards students of SD Negeri 2 Tigajuru specifically in the upper grades is emphasized through habituation and exemplary methods from teachers. These habits are: Starting learning activities with prayer, reading and memorizing juz amma, reading short letters of Al-Quran juz 30. The cultivation of religious character values in Islamic Religious Education learning when learning online is carried out by providing material about: Akidah; Exemplifying the attitude of the Prophet Muhammad PBUH; performing mandatory prayers and purification; About morals. 3) The obstacles faced by online learning such as the lack of teacher control as a patron in providing concrete examples of praiseworthy behavior other than limited to honesty and worship directly to students. Many upper grade students from grades 4 to 5 still cannot recite the Koran and do not even know the prayer recitation, the PAI teacher's capability in learning is limited to assignments without improving learning methods and strategies when online. 4) Character cultivation patterns at SD Negeri 2 Tigajuru teachers still apply a variety of strategies in conventional, lecture-based learning, Suggestions that can be conveyed to teachers related to their role as educators not only provide knowledge. But, also pay attention to the provision of character cultivation through character education, especially in the cultivation of religious character during online learning